Solasodine inhibits invasion of human lung cancer cell through downregulation of miR-21 and MMPs expression. (25th April 2017) - Shen, Kun-Hung; Hung, Jui-Hsiang; Chang, Chia-Wei; Weng, Yu-Ting; Wu, Ming-Jiuan; Chen, Pin-Shern
Abstract: Solasodine, a naturally occurring aglycone of glycoalkaloid in eggplant ( Solanum melongena ), was found to inhibit proliferation in various tumor cells. However, the effect of solasodine on cancer cell metastasis remains unclear. This study investigates the suppression mechanism of solasodine on motility of human lung cancer cell A549 in vitro . Results show that solasodine reduces viability of A549 cells. Treatment with non-toxic doses of solasodine suppresses markedly cell invasion. Solasodine reduces the mRNA level of matrix metalloproteinase-2 (MMP-2), MMP-9 and extracellular inducer of matrix metalloproteinase (EMMPRIN), but increases the expression of reversion-inducing cysteine-rich protein with kazal motifs (RECK), as well as tissue inhibitor of metalloproteinase-1 (TIMP-1) and TIMP-2. Immunoblotting assays indicate that solasodine is effective in suppressing PI3K and Akt phosphorylation. Moreover, solasodine downregulates oncogenic microRNA-21 (miR-21), which has been known to target RECK. Downregulation of miR-21 by miR-21 inhibitor increases RECK expression and decreases cell invasion, suggesting that downregulation of miR-21 by solasodine may contribute to elevate RECK expression and subsequently inhibiting cell invasion. Taken together, the results reveal that inhibition of A549 cell invasion by solasodine may be, at least in part, through blocking MMP expression. Solasodine also reduces PI3K/Akt signaling pathways and downregulates expression of miR-21. These findings demonstrate an attractive therapeutic potential for solasodine in lung cancer anti-metastatic therapy. Highlights: The inhibitory effect of solasodine on invasion of human lung cancer cell is demonstrated. Solasodine downregulates the expression of MMP-2, -9, and EMMPRIN, but increases the expression of TIMP-1, -2 and RECK. Solasodine inhibits the phosphorylation of PI3K and Akt. Downregulation of miR-21 by solasodine may contribute to elevate RECK expression and subsequently inhibiting cell invasion.